Efficacy of breast milk olfactory and gustatory interventions on preterm neonates behaviour responses to pain during heel prick procedures: a hospital-based study - Ringkangmai, Wichamjailiu; Singh, Neeta; Saikia, Bharati; Thakur, Deeksha; Seema; Khanna, Rachna (International Journal of Contemporary Pediatrics, 2025)
Background: Premature infants are particularly vulnerable to stress and pain due to the multiple procedures they undergo in the NICU during a critical phase of brain development. Their heightened sensitivity to tactile stimuli increases the risk of negative effects from frequent medical interventions. Acute pain can have both immediate and long-term neurodevelopmental consequences. This study aimed to assess the impact of breast milk feeding on pain levels during the heel stick procedure in late preterm neonates in selected hospitals of Greater Noida. Methods: A randomized clinical trial compared pain levels in late preterm neonates undergoing a heel stick, with one group receiving breast milk feeding prior to the procedure (n=64) and the other group not (n=64). Pain was assessed using the premature infant pain profile (PIPP) at baseline, 5 minutes and 15 minutes after the procedure. Results: Among 64 late preterm neonates who did not receive breast milk, 79.7% experienced no to minimal pain and 20.3% had minimal to moderate pain, with none experiencing severe pain. In the breast milk feeding group, all 64 neonates reported no to minimal pain during the procedure. 15 minutes post-procedure, the control group reported higher pain (2) than the experimental group (2), with a significant difference (p<0.001). Conclusions: Breast milk feeding is effective in reducing pain during the heel stick procedure in late preterm neonates. This method is a cost-effective and non-pharmacological approach that can be readily adopted to alleviate procedural pain in this vulnerable population.